Governance of Direct-to-User Digital Mental Health Tools: Emphasizing Transparency over Paternalism - Panda, Om D. (The Hastings Center report, 2025)
Digital mental health tools are increasingly used outside traditional clinical settings, creating an engagement paradigm beyond the existing regulatory scope, as noted by Amitabha Palmer and David Schwan in their article “Digital Mental Health Tools and AI Therapy Chatbots: A Balanced Approach to Regulation.” Introducing the direct-to-user concept (which concerns individuals as autonomous agents navigating self-regulation, enhancement, and meaning making), we propose a shift from paternalism and rigid standards critiqued by Palmer and Schwan toward a human-centered governance approach in which radical transparency, individual agency, and shared accountability are themselves the standards. Transparency enables informed choice through intelligible disclosure of data, validity, and incentives, which empower users to assess trade-offs based on personal goals and values. Evolving accountability frameworks, such as voluntary certification with collective liability, reinforce the scalability and ethics of this model, which can also be broadly applied to other digital health tools and cognitive-enhancement technologies. This governance framework fosters individualized, participatory ecosystems to make this new generation of tools more accessible.